1999
DOI: 10.1016/s0928-8244(99)00058-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and immunochemical characterization of limulus factor G-activating substance of Candida spp.

Abstract: The limulus test is a well-established method for the diagnosis of both gram (-) sepsis and invasive fungal infection. To diagnose deep-seated fungal infections, a (1-->3)-beta-D-glucan-specific chromogenic kit (Fungitec G test MK) has been developed and applied clinically. It is suggested that the limulus reactive substance was released from the fungi to the blood, however, its chemical properties were not precisely examined in detail because of the limited quantity available. In this study, we used chemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 13 publications
0
45
1
Order By: Relevance
“…The S. cerevisiae mannan is the neutral fraction, and neither phosphorus nor nitrogen was detected in the specimens, indicating that mannoprotein was not present in the specimens. Mannan fraction from C. albicans IFO 1385 was prepared as described previously (48). Glucan from S. cerevisiae (G-5011) and LPS from Escherichia coli O55:B5 were purchased from Sigma (St. Louis, Mo., U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S. cerevisiae mannan is the neutral fraction, and neither phosphorus nor nitrogen was detected in the specimens, indicating that mannoprotein was not present in the specimens. Mannan fraction from C. albicans IFO 1385 was prepared as described previously (48). Glucan from S. cerevisiae (G-5011) and LPS from Escherichia coli O55:B5 were purchased from Sigma (St. Louis, Mo., U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…To examine the contamination of these fungal cell wall preparations with extraneous LPS, a colorimetric Limulus test (Endospecy test; Seikagaku Co., Ltd., Tokyo) (27) were carried out. Possible contamination of mannan fractions with endogeneous β(1-3)-glucan was examined by Gluspecy test (Seikagaku Co.) (18,48). These results are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…We first cultured C. albicans in a completely synthetic medium in order to obtain water-soluble limulus factor G activating substance that is released from its cells, and obtained a water-soluble polysaccharide fraction released by it into the culture supernatant (C. albicans water-soluble fraction: CAWS), which is thought to be similar to the free β-1,3-D-glucan actually present in patient blood (52). Since the microorganism changes its appearance considerably depending on the culture conditions, observation of the cell wall structure by electron microscopy confirmed that it adopted a structure similar to natural media ( Fig.…”
Section: Water-soluble Limulus Factor G Activating Substance Cawsmentioning
confidence: 99%
“…This is a useful animal model of KD, since it exhibits many histological similarities to KD [6,7]. On the other hand, Ohno et al reported unique biologic characteristics for substances obtained from the C. albicans water-soluble fraction (CAWS) [8][9][10]. Studies in mice demonstrated that CAWS induced vasculitis at a clearly higher incidence than CADS, and that the vasculitis was histologically similar to that induced by CADS [11,12].…”
Section: Introductionmentioning
confidence: 99%